2018
DOI: 10.1186/s13690-018-0265-5
|View full text |Cite
|
Sign up to set email alerts
|

The burden and high prevalence of hypertension in Pakistani adolescents: a meta-analysis of the published studies

Abstract: BackgroundHypertension has been recognized as a global health concern for developing countries and is scarcely described in many of these countries. In Pakistan, few population-based surveys evaluated the prevalence of hypertension and there is no current nationally representative study (the latest nationwide survey was conducted more than two decades ago). Objective: The goal of the current study was to estimate the pooled prevalence of hypertension in Pakistani population using meta-analysis approach.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 36 publications
(44 reference statements)
6
57
3
Order By: Relevance
“…This systematic review and meta-analysis revealed that the pooled prevalence of hypertension in Ethiopia was 21.81% (95% CI: 19.20–24.42), which was consistent with a study conducted in rural communities of Sub-Saharan Africa (22%), Kenya (22.8%), and a meta-analysis from Vietnam (21.1%) [ 62 64 ]. However, the finding of this meta-analysis was lower than the previous meta-analysis reports in LMICs (32.3%), among adults in Africa (57.0%), a meta-analysis study on undiagnosed hypertension in Sub-Saharan Africa (30%), Nigeria (28.9%), India (29.8%), Pakistan (26.34%), and a study in Nepal (25.1%) [ 65 71 ]. The prevalence of hypertension in this review was higher than a study conducted a previous systematic review in Ethiopia and a study conducted in Ghana [ 13 , 72 ].…”
Section: Discussioncontrasting
confidence: 72%
“…This systematic review and meta-analysis revealed that the pooled prevalence of hypertension in Ethiopia was 21.81% (95% CI: 19.20–24.42), which was consistent with a study conducted in rural communities of Sub-Saharan Africa (22%), Kenya (22.8%), and a meta-analysis from Vietnam (21.1%) [ 62 64 ]. However, the finding of this meta-analysis was lower than the previous meta-analysis reports in LMICs (32.3%), among adults in Africa (57.0%), a meta-analysis study on undiagnosed hypertension in Sub-Saharan Africa (30%), Nigeria (28.9%), India (29.8%), Pakistan (26.34%), and a study in Nepal (25.1%) [ 65 71 ]. The prevalence of hypertension in this review was higher than a study conducted a previous systematic review in Ethiopia and a study conducted in Ghana [ 13 , 72 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Better disease knowledge and awareness about potential complications among university graduates may explain higher likelihood to attend treatment follow-up visits. [38] 190 [62] Secondary care hospital 203 123 [61] 80 [39] Primary healthcare centre 151 33 [22] 118 (78) Overall 662 274 [41] 388 [59] Entitlement to free medical care…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the pooled prevalence was 24.9% (19.70-30.28%) in males and 24.7% (16.76-32.76%) in females. 8 Poor adherence is a critical barrier to treatment success [9][10][11] leading to worsening of disease, increased hospitalization rate and longer hospital stays. The estimated overall global prevalence of non-adherence to antihypertensive therapy is around 30%.…”
Section: Introductionmentioning
confidence: 99%